Molecular disruption of neuroinflammatory and metabolic pathways mediates triclosan-induced depressive-like behavior in zebrafish - Danting Wang; Junping Liu; Ruixue Zhou; Bing Han; Chunxia Chen; Wentong Meng; Li Qin; Limei Sun; Bin Tan; Chunyan Huang (Toxicology and Applied Pharmacology, 2026)

Structure–function relationship of Konjac glucomannan with varying acetylation degrees in modulating gut microbiota and alleviating prediabetes - Hongchao Wang; Yurong Zhao; Danting Dang; Liming Huang; Zhangming Pei; Jianxin Zhao; Hao Zhang; Wei Chen; Wenjun Wu; Wenwei Lu (Carbohydrate Polymers, 2026)

Kinetic simulation of NOx reduction in cement pre-calciner environment: Synergistic effect of multi-reductant, catalytic effect of raw meal, and their reaction mechanism - Hui Peng; Junyi Zhou; Rongyu Wu; Tongsheng Zhang; Danting Chen; Yue Tang; Congxi Tao; Jiangxiong Wei; Qijun Yu (Chemical Engineering Journal, 2025)

Co-exposure to triclosan and polystyrene nanoplastics on neurodevelopmental toxicity and gut microbiota dysbiosis in zebrafish (Danio rerio) - Danting Wang; Junying Lan; Wentong Meng; Junping Liu; Ruixue Zhou; Chunxia Chen; Li Qin; Bin Tan; Chunyan Huang (Environmental Pollution, 2025)

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

Are Mini and full-size electric vehicle adopters satisfied? An application of the regression with dummy variables - Danting Zhao; Yuandong Liu; Hong Chen (Travel Behaviour and Society, 2024)

Trophic relationship between mussels and scale worms under various seepage intensities in the haima cold seep: Insights from stable isotopes (δ13C and δ15N) and C:N:P stoichiometry - Zhixin Ke; Haochen Huang; Danting Chen; Yehui Tan (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

In silico, in vitro and in vivo safety assessment of three Limosilactobacillus mucosae strains for probiotic candidates - Danting Dang; Xiaoming Liu; Haiqin Chen; Jianxin Zhao; Wei Chen; Bo Yang (Food Bioscience, 2024)

The root-associated Fusarium isolated based on fungal community analysis improves phytoremediation efficiency of Ricinus communis L. in multi metal-contaminated soils - Huaxiong Yao; Wenguang Shi; Xing Wang; Junyan Li; Meiqi Chen; Jianbin Li; Danting Chen; Lin Zhou; Zujun Deng (Chemosphere, 2023)

Spatial and Seasonal Variations in the Stable Isotope Values and Trophic Positions of Dominant Zooplankton Groups in Jiaozhou Bay, China - Zhixin Ke; Ruofei Li; Danting Chen; Chunyu Zhao; Yehui Tan (Frontiers in Marine Science, 2022)
The spatial and seasonal distributions of stable carbon and nitrogen isotopes (δ 13 C and δ 15 N) in dominant zooplankton groups were investigated in Jiaozhou Bay. Zooplankton δ 13 C values ranged from −22.89‰ to −15.86‰, and δ 15 N values ranged from 3.18‰ to 13.57‰, respectively. The δ 13 C and δ 15 N values generally followed the order of small zooplankton < large calanoids < small Sagitta < large Sagitta . Spatial distribution patterns of zooplankton δ 13 C and δ 15 N values varied in different seasons. Our results suggested that the spatial variation of δ 13 C was mainly controlled by terrigenous organic matter (OM) input and phytoplankton biomass, but water temperature may have played a key role in the seasonal variation of δ 13 C. In spring, the high phytoplankton biomass might increase the δ 13 C value of small zooplankton in the inner bay. During other seasons, the δ 13 C values of zooplankton generally increased from the inner bay to the outer bay, which might be associated with the influence of 13 C-depleted terrigenous OM carried by the river discharge. Small zooplankton stable isotope values were significantly correlated with that of particulate organic matter (POM). The influence of anthropogenic nutrient input on isotopic baseline can be cascaded to the zooplankton, and the effect might be weak at higher trophic levels. The Bayesian standard ellipse areas of dominant zooplankton groups were generally smallest in the winter, suggesting a narrow niche width during that time. The niche partition between small zooplankton, large calanoids, and Sagitta was most distinct in winter, and followed by summer. The relative trophic level of Sagitta ranged from 2.23 to 4.01, which generally declined from the inner bay to the outer bay during the spring, autumn, and winter seasons. High anthropogenic nutrient loading might reduce the difference in trophic niches among zooplankton groups. This study provided detailed information on the distribution of zooplankton δ 13 C and δ 15 N in a coastal bay, which will be useful for understanding the anthropogenic influence on the ecosystem structure and function.

Ribosomal ITS sequence-directed selection for endophytic Myrothecium strains antagonistic to Ralstonia solanacearum to control patchouli bacterial wilt - Wenguang Shi; Jiaqi Li; Huaxiong Yao; Jianbin Li; Meiqi Chen; Danting Chen; Yinghao Fu; Huarong Xie; Zujun Deng (BioControl, 2022)

Distribution of C/N/P stoichiometry in suspended particulate matter and surface sediment in a bay under serious anthropogenic influence: Daya Bay, China - Danting Chen; Zhixin Ke; Yehui Tan (Environmental Science and Pollution Research, 2021)

Geochemistry of heavy metal-contaminated sediments from the Four River inlets of Dongting lake, China - Xiaohong Fang; Bo Peng; Zhaoliang Song; Sicheng Wu; Danting Chen; Yafang Zhao; Jing Liu; Yanan Dai; Xianglin Tu (Environmental Science and Pollution Research, 2021)

Deep Eutectic Solvents Based Ultrasonic Extraction of Polysaccharides from Edible Brown Seaweed Sargassum horneri - Jinggui Nie; Danting Chen; Yanbin Lu (Journal of Marine Science and Engineering, 2020)
In this work, a method for ultrasonic extraction of polysaccharides from Sargassum horneri using deep eutectic solvents was proposed. The studied deep eutectic solvents were composed of choline chloride, 1,2-propanediol and water. Based on the single-factor experiment results, four experimental factors were systematically evaluated, giving the optimal extraction conditions as follows: molar ratio of choline chloride to 1,2-propanediol of 1:2, water content of 30% (v/v), solid-liquid ratio of 1:30 (g/mL), and the extraction temperature of 70 °C. Fourier transform infrared spectroscopy and X-ray diffraction were utilized to investigate changes in the chemical characteristic of extracted polysaccharides. The results indicated that deep eutectic solvents had stronger protein and calcium carbonate removal ability than that of a conventional hot water extraction method. Moreover, in vitro antioxidant activity tests exhibited that the obtained polysaccharides had significant inhibition effects on DPPH and ABTS radicals. The proposed deep eutectic solvents assisted ultrasonic extraction protocol was considered to be a green, fast and effective protocol for extracting polysaccharides from Sargassum horneri.

Understanding driving patterns of carbon emissions from the transport sector in China: evidence from an analysis of panel models - Danting Lin; Lanyi Zhang; Cheng Chen; Yuying Lin; Jiankai Wang; Rongzu Qiu; Xisheng Hu (Clean Technologies and Environmental Policy, 2019)

Fine mapping of S32(t), a new gene causing hybrid embryo sac sterility in a Chinese landrace rice (Oryza sativa L.) - Danting Li; Liangming Chen; Ling Jiang; Susong Zhu; Zhigang Zhao; Shijia Liu; Ning Su; Huqu Zhai; Hiroshi Ikehashi; Jianmin Wan (Theoretical and Applied Genetics, 2007)